THE INFLUENCE OF EMPLOYEE KNOWLEDGE SKILL ABILITY TO TEAM PERFORMANCE AT PT. EQUITYWORLD FUTURES MANADO - Siwy, Gracia; Pangemanan, Sifrid S.; Tielung, Maria V.J. (FEB Universitas Sam Ratulangi Manado, 2019)
Abstract: Human resources is an important asset for a company or organization, with the existence of employees it helps to achieving the vision and mission. Employee competencies can be seen from KSA, such as knowledge, skill and abilities and each employees have differences one to another it is also happen for knowledge, skill and ability of the employees. Employees of the company are lack in understanding the work, difficult to adjusts the work due the educational background is not related with the work, not able to interact well with each other related with the work, can't determine how to complete a task properly, unable to take the initiative to do the work and unable to work under pressure. This research is aims to find the influence of employee knowledge, skill and ability to team performance at PT. Equityworld Futures Manado. Causal analysis type and used random sampling technique with 73 respondents. This research used multiple linear regression to test the data. The results shows variables of knowledge, skill and ability has influence to team performance at PT. Equityworld Futures Manado. The company have to improve the human resource department, the company have to focus more in recruiting new employees in order to find competent employees.Â Keywords: knowledge, skill, ability, team performance